Phytosterol Composition in Various Kinds of Red Beans Processing (Vigna angularis) - Sugijanto Kartosentono (Journal of Global Pharma Technology, 2020)
The high level of blood cholesterol can be overcome by consuming phytosterols obtained from plants, especially nuts. One of the leading beancommodity in the society is red beans (Vignaangularis). This study aims to identify the content of phytosterols in red beans and the processing effect of phytosterols. Red beans sample which has been processed, was extracted with n-hexane, acetone, and hydrolyzed. The results of sample extraction were analyzed using the 6890 Series Agilent Gas Chromatography instrument with a Flame Ionization Detector (FID) and HP-5 column (5% Phenyl, 95% Methyl Siloxane). Phytosterol content in the form of campesterol, stigmasterol, and sitosterol was found in red bean samples. The most composition of stigmasterol was found in baked samples and significantly different from boiled samples (p